Correlation Between the Radiation Fractionation Number and the Major Nursing Problems in Cervical Cancer Patients Undergoing External Radiation - Yulia Kusuma Indah; Handayani Handayani; Yoanita Hijriyati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aim: The purpose of this study is to identify the correlation between the radiation fractionation number and the major nursing problems in cervical cancer patients with external radiation. Method: This research design was quantitative descriptive using the cross-sectional approach. Consecutive sampling was applied to collect data from 45 cervical cancer patients who were undergoing external radiation at Radiotherapy Department of Dharmais Cancer Hospital, taken from January to April 2019. The inclusive respondents fulfilled the instruments including questionnaire to determine the number of radiation fractionation and the problems that the patients were experiencing. Univariate data analysis used frequency distribution technique and bivariate used Spearman’s rank correlation. Result: The study results indicate that the majority of irradiated cervical cancer patients were aged 41-60 years, in advanced stage of III B, and they did not receive surgery therapy before radiotherapy. There is a correlation between the radiation fractionation number and the major nursing problems in irradiated cervical cancer patients where the P value is 0.000 (r=0.713). They experienced major nursing problems of distress/coping in the 5th fractionation, nutrition alteration in the 10th fractionation, impaired skin integrity and nutrition alteration in the 15th fractionation, while in the 20th and 25th fractionations, the major problem was impaired skin integrity. Conclusion: The study depicted a significant and strong positive correlation between the radiation fractionation number and the major nursing problems in irradiated cervical cancer patients, the higher radiation fractionation level, the higher (severe) the nursing problem.  The study suggests nurses to conduct further study on the side effects of radiation to improve nursing care for irradiated cancer patients.